Between Vulnerability and Deservingness: Social Imaginaries About Migrants Among Primary Health Care Nurses - Ángel Martín-García; Cristina Oter-Quintana; Milagros Rico-Blázquez; Fernando Jesús Plaza del Pino; María Idoia Ugarte-Gurrutxaga (Healthcare, 2026)
Background/Objectives: Primary Health Care is central to universal health coverage and equity. Nurses can facilitate effective accessibility, but their social imaginaries may influence clinical interaction and the perceived legitimacy of migrants’ demands. The aim of this study was to understand how Primary Care nurses construct social imaginaries about migrants. Methods: An interpretive qualitative study informed by a critical anthropological perspective was conducted. Eight Primary Health Care nurses participated. Purposive sampling was followed by snowball sampling. Between January and July 2025, in-person semi-structured interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Three themes were identified: (1) the construction of otherness; (2) the migration process; and (3) the “luck” of having healthcare and not being able to demand it. Participants’ discourses combined vulnerability and racialized differentiation with narratives of perceived abuse, deservingness, expected gratitude, and possible informal forms of access regulation. Conclusions: Across the three themes, social imaginaries simultaneously constructed migrants as vulnerable and as users suspected of abuse, linking these representations to judgments of deservingness and the legitimacy of healthcare demands. Primary Health Care nurses may act as facilitators or informal barriers to effective accessibility, supporting culturally sensitive, compassionate, anti-racist, and migrant-sensitive healthcare.